(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
By following electron beam gun evaporation technique, the magnetic multilayers in the configuration, [Mn(60nm)/Al(20nm)]n; n =1, 2 and 9 were deposited at 473K,Â under high vacuum conditions. From grazing incidence X- ray diffraction (GIXRD) studies, the grain sizes were determined and they were in the order of few nanometers. Atomic force microscope (AFM) were employed to study surface structure and grain sizes. The magnetization as a function of field at 150K and 200K have been measured using the MPMS SQUID - vibrating sample magnetometer (VSM). From the hysteresis loops, coercive field, saturation magnetization, remanent magnetization and antiferromagnetic coupling were determined. All the three films hinted at the existence of at antiferromagnetic interaction between Mn layers through Al layer. Electrical resistivity in the temperature range from 5K to 300K has been measured. Films exhibited semiconducting to metallic transition. The power law variation of resistivity with temperature was established for the metallic region. Conductivity data for semiconducting region of a film has been analysed using polaran hopping models, activation energy and density of states at Fermi level were established. This is for the first time that antiferromagnetic coupling between Mn layers through interfacer layer and semiconducting to metallic transition have been noticed in the present configuration of [Mn/Al] multilayers.